Practical guide to monitoring anaesthetised small animal patients. Issue 8 (1st September 2016) - Mathis, Alessandra
Abstract : Anaesthesia – a reversible and controlled coma‐like state – is an art based on an understanding of many contributing factors: pharmacology, the patient and its varied physiological processes or disease states, the procedure being undertaken and the potential complications arising as a result of all of these. Monitoring a patient at this time can be challenging but the increasing use of multiparameter monitors reduces the incidence of morbidity and mortality in both people and animals. Understanding the data displayed on these monitors is important, but it is vital not to lose sight of the whole picture as well. This article focuses on the main parameters that are monitored when small animals undergo general anaesthesia (including the patient itself) and explains how the data acquired should be considered in relation to other information.